Moč mišične kontrakcije, izvabljene z električno stimulacijo - Novak, Primož (Rehabilitacija (Ljubljana), 2016)
Background: Neuro-muscular electrical stimulation is frequently used for therapeutic purposes. Data on muscle strength improvement using electrical stimulation of different intensities differ widely in the literature. With increasing intensity, stimulation becomes unpleasant and painful. The pain threshold differs between individuals; different muscle force contraction can therefore be expected at pain threshold. The goal of our study was to find out what is the strength of quadriceps contraction, evoked by electrical stimulation bellow the pain threshold (i.e., electrical stimulation of maximal tolerance), compared to the strength achieved at maximal voluntarily isometric contraction of the same muscle group. Methods: Twelve healthy male volunteers, aged 22 to 73, were included in the study. Torques of knee extensors at maximal voluntarily isometric contraction and during electrical stimulation of maximal tolerance without voluntarily contraction was measured for both knees. Results: Average knee extensors torque during electrical stimulation of maximal tolerance was 34.2 Nm (15% of the value of maximal voluntarily isometric contraction) on the right side and 39.9 Nm (18% of value of maximal voluntarily isometric contraction) on the left side. Neither of the parameters exhibited a clear correlation with age. Conclusions: With electrical stimulation of maximal tolerance, quadriceps contraction of approximately 1/6 of the torque achieved at maximal voluntarily isometric contraction of the same muscle was evoked. There were large differences in response between participants, therefore electrical stimulation parameters should be adjusted to each patient.
Keywords: Electric Stimulation Therapy; električna stimulacija; isokinetic contraction; izometrična kontrakcija; mišična kontrakcija; Muscle Contraction; Navar; navor; neuro-muscular electrical stimulation maximal tolerance; torque